An analysis on the connections of factors in a public transport system by AHP-ISM - Duleba, Szabolcs; Shimazaki, Yoshiaki; Mishina, Tsutomu (Transport, 2013)
In order to gain an overall view on all relevant connections of the elements in a public transportation system, a systematic approach is advisable to follow, which applies well-proven methodology. In case a structure contains both hierarchical and non-hierarchical connections, the formerly recommended methodologies are: ISM-AHP, ISM-ANP, ANP. This paper however proposes a different approach: AHP-ISM, which aims to keep the AHP hierarchy, but simul- taneously to amend that with the non-hierarchical types of linkages within the structure. By that, those connections that were verified in the AHP procedure can be considered dominant, but also weaker linkages might provide impor- tant additional information about the whole structure. The additional ISM procedure is suitable for two purposes: the most influential elements of the AHP structure can be selected, moreover also direct and indirect impacts of element improvement might be followed in the structure by considering both types of connections within the system, using the directed graph of ISM. The introduced AHP-ISM model is applicable for analyzing public transportation systems – as shown in the paper – but also generally applicable for any AHP applications, which are not strictly but dominantly hierarchically structured. First Published Online: 24 Dec 2013